History Education at the Pandemic School. Towards a Pedagogy of Emergency - Plá, Sebastián (Universidad Nacional del Litoral, 2020)
In this essay, I discuss what history education can do against the Covid-19 pandemic. I focus my attention in the educational dimension of history education, instead of the disciplinary knowledge. Also, I analyze the school conditions produced by the health control, overall the schools lock down and the isolate of students and teachers. For that, I describe the history education as flied of research, the situation of the school in Mexico, and I try to define some features of history education. Finally, I point out suggestion for acting in three levels. Fist, the instructional, second the curricular and third the structural. All three level use de curricular justice as framework and educational aims. All these suggestions are part of what I call pedagogy for the emergency.